Efficacy and safety of Cordyceps sinensis (Hirsutella sinensis, Cs-C-Q80) in chronic bronchitis - Shu, Xinyang; Xu, Dongfeng; Qu, Yumin; Shang, Xiaofeng; Qiao, Kehong; Feng, Cuiling; Cui, Hongsheng; Zhao, Xianping; Li, Yuxin; Peng, Yu; Li, Demin; Zhang, Hongchun (Frontiers in Pharmacology, 2024)
Background: Cordyceps sinensis is a traditional Chinese medicine that has shown promise for the management of chronic bronchitis (CB). We aim to assess the efficacy and safety of a preparation of C. sinensis named Bailing capsule (Hirsutella sinensis, Cs-C-Q80) compared with a placebo in patients with CB. Methods: This randomized, double-blind, placebo-controlled, parallel-group clinical trial (Chinese Clinical Trial Registry; registration number: ChiCTR1900025707) recruited patients with CB from eight hospitals in China between May 2019 and December 2020. Patients were randomized 2:1 to receive Bailing capsule or a placebo orally for 48 weeks (2.0 g, three times a day). Results: Among 240 patients who were randomized, 238 (Bailing capsule: 159, placebo: 79) were included in the primary analysis. Bailing capsule significantly reduced the frequency of acute exacerbation of CB (AECB) compared with the placebo during treatment (0.43 ± 0.82 vs. 1.56 ± 1.34; P < 0.001) and follow-up (0.21 ± 0.64 vs. 0.45 ± 0.93; P = 0.026). Bailing capsule improved the severity of expectoration (P = 0.046) and wheezing (P = 0.010) in AECB during follow-up. The severity of CB after treatment was significantly improved in the Bailing capsule group compared with the placebo group (P = 0.035), particularly in terms of expectoration (P = 0.012) and wheezing (P = 0.003). The risk of adverse events, mainly including infectious and invasive diseases and gastrointestinal symptoms, did not significantly differ between the two groups (29.6% vs 30.4%). Conclusions: In patients with CB, Bailing capsule significantly reduces the frequency of AECB and ameliorates the severity of AECB and CB symptoms.